2014
DOI: 10.1063/1.4890212
|View full text |Cite
|
Sign up to set email alerts
|

Time evolution studies of laser induced chemical changes in InAs nanowire using Raman spectroscopy

Abstract: We report the study of time evolution of chemical changes on the surface of an InAs nanowire (NW) on laser irradiation in different power density regime, using Raman spectroscopy for a time span of 8–16 min. Mixture of metastable oxides like InAsO4, As2O3 are formed upon oxidation, which are reflected as sharp Raman peaks at ∼240–254 and 180–200 cm−1. Evidence of removal of arsenic layer by layer is also observed at higher power density. Position controlled laser induced chemical modification on a nanometer sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…The oxidation process consists of several parallel reaction schemes, where each scheme typically includes two sequential reactions [19,28]. Let us first consider the oxidation reaction kinetics of InAs surfaces in general terms, valid for all possible reactions including InAs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxidation process consists of several parallel reaction schemes, where each scheme typically includes two sequential reactions [19,28]. Let us first consider the oxidation reaction kinetics of InAs surfaces in general terms, valid for all possible reactions including InAs.…”
Section: Resultsmentioning
confidence: 99%
“…To this end, locally accelerating the reaction by focused laser irradiation has been demonstrated and can be combined with micro-Raman spectroscopy to provide information about the vibrational modes of individual semiconductor nanowires [8][9][10][11] and also conveying information about the elemental composition [12,13], crystal properties [14], and defects [15] as well as free carrier densities and mobilities [16]. Also, at high intensities, focused laser irradiation has been shown to enable controlled local cutting or chemical modification of InAs and GaAs nanowires by local oxidation and formation of crystalline arsenic [17][18][19][20][21] and enables welding of metal nanowires [22]. This opens the possibility for using focused laser beams for simultaneous micro-Raman characterization and engineering new functionality into nanowire devices.…”
Section: Introductionmentioning
confidence: 99%
“…[25] Therein, we show that blue shift and reduction in FWHM at higher powers (6 mW), whereas, larger redshift and increase in FWHM are expected, if it was due to heating. [25] Further, for~0.3 mW, no change was observed over time evolution of 8 min. The effect of confinement is also rejected because the diameters we are studying that are much beyond phonon confinement effects are expected to occur (<200 nm).…”
Section: Resultsmentioning
confidence: 58%
“…Raman spectroscopy is especially useful for study of MNWs, as density of MNWs is low, and it is difficult to study them using more conventional techniques, like X-ray diffraction. In our earlier study of laser power-dependent time evolution of Raman spectra of InAs MNW (diameter (d)~1 μm), a TO like mode~214 cm À1 [25] was noted, whereas, for bulk InAs, TO phonon wavenumber is 217.5 cm À1 . [26] In the present study, we have investigated this observed red shift in InAs MNW, using spatially resolved Raman spectroscopy (SRRS) on several MNWs of a different kind.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach which has recently emerged is the possibility of using a high intensity focused laser beam to locally induce chemical changes in the NW 14 . By combination of Raman spectroscopy 15 and transmission electron microscopy 16 it has been established that for the case of InAs the high intensity laser, in the presence of ambient air conditions, promotes the oxidation process As 2 O 3 +2InAs→In 2 O 3 +4As which converts the irradiated parts of the NW surface to crystalline arsenic and polycrystalline indium oxide 16 . However, so far, only little is known about the properties of the resulting structures and the spatial resolution that can be achieved has not been analyzed.…”
mentioning
confidence: 99%